2019
DOI: 10.1192/bjb.2018.116
|View full text |Cite
|
Sign up to set email alerts
|

Against the stream: intermittent nurse observations of in-patients at night serve no purpose and cause sleep deprivation

Abstract: This paper argues that intermittent nursing observations of in-patients at night do not reduce the risk of suicide or severe self-harm. Suicides between 23.00 h and 07.00 h are rare, and these overwhelmingly occur under intermittent observations. Such observation is purely a defensive intervention to document that a patient is safe at a particular time, as there is no engagement. For the large majority of in-patients, it has the unintended consequence of causing sleep deprivation. The intervention may cause ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
1
14
0
1
Order By: Relevance
“…In fact, some have even suggested that, given their negative impact on patient care, intermittent nursing observations, in their current form, should be abandoned. 19 Artificial intelligence (AI) could provide a solution to these issues, 20 but its introduction in mental healthcare requires careful evaluation and implementation. 21…”
Section: Introductionmentioning
confidence: 99%
“…In fact, some have even suggested that, given their negative impact on patient care, intermittent nursing observations, in their current form, should be abandoned. 19 Artificial intelligence (AI) could provide a solution to these issues, 20 but its introduction in mental healthcare requires careful evaluation and implementation. 21…”
Section: Introductionmentioning
confidence: 99%
“…These night-time intrusions have been shown to further worsen sleep and potentially increase the patient's sensitivity to light, noise or other disturbances (Park 2018). Moreover, these in-patients are likely to be exposed to increased lux at night-time (because lights are repeatedly switched on to enable observation), which is potentially countertherapeutic (Veale 2019). However, a system that requires no direct patient contact but allows staff to closely and continuously monitor individual patients uses ultra-wideband radar technology that is built into the ceiling of patients' rooms.…”
Section: Major Innovationmentioning
confidence: 99%
“…All treated had either paranoid schizophrenia, psychosis or depressive disorder, reflecting the typical case mix of the two wards. Mean insomnia severity index before treatment was 18 (range 6-28), and completion insomnia severity index was 14 (range [6][7][8][9][10][11][12][13][14][15][16].…”
Section: Cbtimentioning
confidence: 99%
“…Understandable concern about patient safety is one reason for frequent physical checks, despite no direct evidence that fixed timing checks reduces risk. 7,8 After review of current observation policy across a large mental health trust, a pilot scheme to enhance sleep was introduced (the SleepWell programme). This was a package including reduction of overnight noise and light, formal staff education about sleep and sleep disorders, a protected sleep period for those deemed safe and screening for sleep apnoea and restless legs syndrome for all in-patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation